Synthesis and optoelectronic properties of quinoidal 2,2',6,6'-tetraphenyldipyranylidene towards photovoltaic applications - Courté, Marc (2018)
Organic solar cells (OSCs) and more recently perovskite solar cells (PSCs) have attracted a great attention in the scientific field of photovoltaics due to their potential low cost, simple fabrication process and promising power conversion efficiency (PCE). With excitons photogeneration processes, the charge carrier extraction is an essential step in the good operation of photovoltaic solar cells. Interfacial layers, such as hole transporting layer are commonly used to promote the charge diffusion towards the electrodes, resulting of a higher photocurrent. Consequently, the development of novel hole transport materials (HTMs) with suitable optoelectronics properties, low–cost and simple synthetic pathway is a major ongoing research to achieve highly efficient OSCs and PSCs. In this thesis, 2,2’,6,6’-tetraphenyldipyranylidene (DIPO-Ph4), a large quinoidal planar π-conjugated heterocycle is presented. The synthesis and characteristics of DIPO-Ph4 are described in details, in particular the electrical characteristics which are investigated in a field-effect transistor configuration. A suitable HOMO level energy and good hole transport properties make DIPO-Ph4 a potential candidate to be used as an efficient hole-transporting material (HTMs) in organic or perovskite solar cells. The presented results will demonstrate that dipyranylidene core could be an excellent building block for high mobility HTMs.